The “Pocket book of primary health care for children and adolescents”: WHO standards for improving paediatric and adolescent primary care in Europe, Central Asia and worldwide - Krüger, Carsten; Huss, Gottfried; Yasmin, Farzana; Weigel, Ralf (Frontiers in Pediatrics, 2024)
Paediatric primary care is more frequently provided both by physicians other than specialised paediatricians as well as non-physician cadres in Europe and globally. The quality of paediatric primary care including a focus on preventive measures is rather variable and often does not comply with agreed international standards. WHO Europe developed standards for paediatric primary care applicable to the WHO Europe region and globally to improve the provision and outcome of paediatric primary care across all settings. These standards were published in an open-access pocketbook and in an open-access app, both accessible free-of-charge. Although originally intended for use in the WHO Europe region, the pocketbook provides valuable information for all settings of paediatric primary care worldwide.